Volatile compound changes during shelf life of dried Boletus edulis: comparison between SPME‐GC‐MS and PTR‐ToF‐MS analysis. (19th January 2015) - Aprea, Eugenio; Romano, Andrea; Betta, Emanuela; Biasioli, Franco; Cappellin, Luca; Fanti, Marco; Gasperi, Flavia
<x xml:space="preserve">Abstract</x> Drying process is commonly used to allow long time storage of valuable porcini mushrooms (Boletus edulis). Although considered a stable product dried porcini flavour changes during storage. Monitoring of volatile compounds during shelf life may help to understand the nature of the observed changes. In the present work two mass spectrometric techniques were used to monitor the evolution of volatile compounds during commercial shelf life of dried porcini. Solid phase microextraction (SPME) coupled to gas chromatography ‐ mass spectrometry (GC‐MS) allowed the identification of 66 volatile compounds, 36 of which reported for the first time, monitored during the commercial shelf life of dried porcini. Proton transfer reaction ‐ time of flight ‐ mass spectrometry (PTR‐ToF‐MS), a direct injection mass spectrometric technique, was shown to be a fast and sensitive instrument for the general monitoring of volatile compound evolution during storage of dried porcini. Furthermore, PTR‐ToF‐MS grants access to compounds whose determination would otherwise require lengthy pre‐concentration and/or derivatization steps such as ammonia and small volatile amines. The two techniques, both used for the first time to study dried porcini, provided detailed description of time evolution of volatile compounds during shelf life. Alcohols, aldehydes, ketones and monoterpenes diminish during the storage while carboxylic acids, pyrazines, lactones and amines increase. The storage temperature modifies the rate of the observed changes influencing the final quality of the dried porcini. We showed the advantages of both techniques, suggesting a strategy to be adopted to follow time evolution of volatile compounds in food products during shelf life, based on the identification of compounds by GC‐MS and the rapid time monitoring by PTR‐ToF‐MS measurements in order to maximize the advantages of both techniques. Copyright © 2015 John Wiley & Sons, Ltd.